A Distributed Algorithm for Optimising over Pure Strategy Nash Equilibria - Chapman, Archie; Farinelli, Alessandro; Munoz de Cote, Enrique; Rogers, Alex; Jennings, Nicholas (Proceedings of the AAAI Conference on Artificial Intelligence, 2010)
We develop an efficient algorithm for computing pure strategy Nash equilibria that satisfy various criteria (such as the utilitarian or Nash-Bernoulli social welfare functions) in games with sparse interaction structure. Our algorithm, called Valued Nash Propagation (VNP), integrates the optimisation problem of maximising a criterion with the constraint satisfaction problem of finding a game’s equilibria to construct a criterion that defines a c-semiring. Given a suitably compact game structure, this criterion can be efficiently optimised using message-passing. To this end, we first show that VNP is complete in games whose interaction structure forms a hypertree. Then, we go on to provide theoretic and empirical results justifying its use on games with arbitrary structure; in particular, we show that it computes the optimum >82% of the time and otherwise selects an equilibrium that is always within 2% of the optimum on average.